SUBJEKTO TAPSMAS GALIOS IR TIESOS SANKIRTOJE: MICHELIO FOUCAULT POŽIŪRIS. - ŠLIUŽAITĖ, VILMA (Logos: A Journal, of Religion, Philosophy Comparative Cultural Studies & Art (08687692), 2025)
The article analyses Michel Foucault's approach to the becoming of the subject at the intersection of power and truth. Foucault argues that truth never exists independently of power: so-called "regimes of truth" not only underpin certain forms of knowledge but also function as mechanisms that shape the subject through discipline and control. Foucault's radical refusal to acknowledge the essentialist, autonomous nature of the subject focuses on the subject as the ever-changing product of discursive practices, power relations and truth regimes. This approach reveals how subjectivity is shaped in the interplay between technologies of power and structures of knowledge. However, in his late work, Foucault turns to the question of ethical self-creation, proposing the subject as a critically reflective being capable of turning inwards, rethinking its relation to dominant regimes of truth and creating itself through ethical practice. However, while this ethical position opens the possibility of autonomy and self-responsibility, Foucault fails to liberate the subject from the regimes of truth shaped by power structures. The becoming of a subject whose identity is not grounded in nature is not an authentic growth, but rather a self-creation with no moral or existential basis.